Enhancing Enhancing The Eighth Grade Students Reading Compehension Achievement By Using Question-Answer Relationship (QAR) Strategy - Sari, Shinta Permata; Rofiq, Annur; Suharjito, Bambang (EFL Education Journal, 2022)
This research was aimed at improving the eighth-grade students’ reading achievement and their participation during teaching-learning process using the Question-Answer Relationship (QAR) Strategy. This research applied Classroom Action Research (CAR) design with grade eight students of secondary school at junior high school as the research participants. The data were analyzed using descriptive statistics to know the improvement of the students’ reading comprehension achievement and the students’ participation after being taught reading using QAR strategy. This research was conducted in 1 cycle consisted of five meetings. The result of this research showed that the use of QAR Strategy could improve the students’ reading comprehension achievement and the students’ participation during the teaching and learning of reading.